MPS 12-04 RESFEM STUDY: CHRONIC TRANS-RESVERATROL SUPPLEMENTATION IMPROVES CEREBRAL VASODILATOR RESPONSIVENESS (CVR) AND COGNITION IN POST-MENOPAUSAL WOMEN. (September 2016) - Evans, Hamish; Howe, Peter; Wong, Rachel
Abstract : Objective: Loss of beneficial effects of estrogen on the cerebrovasculature may contribute to the heightened risk of dementia in postmenopausal women. We examined the relationship between cerebrovascular function and cognition in this population and tested whether supplementation with resveratrol (a phytoestrogen) could improve their CVR and cognitive performance. Design and Method: Eighty postmenopausal women aged 45–85 years were randomised to take resveratrol (2 × 75 mg/day) or placebo for 14 weeks and changes in the following were assessed:-. cognitive performance in domains of executive function, semantic, verbal and visuospatial working memory; transcranial Doppler ultrasound recording of blood flow velocity (BFV) in the middle cerebral artery, pulsatility index (PI, a measure of arterial stiffness) and CVR (percent increase of BFV) to both cognitive testing and hypercapnia (breathing carbogen gas for 3 min). Results: At baseline, a composite score of cognitive performance correlated with basal BFV (R = 0.340, P = 0.005), CVR to cognitive stimuli (R = 0.345, P = 0.006) and inversely with PI (R = −0299, P = 0.029). Compared to placebo, supplementation with resveratrol elicited 17% increases in CVR to both the hypercapnic (P = 0.018) and cognitive stimuli (P = 0.036). The latter was an overall response; there were also increases in CVR to individual tests of semantic (P = 0.003) verbal memory (P = 0.021) and executive function (P = 0.048). Moreover, resveratrol improved overall cognitive performance (P = 0.010). Conclusions: This is the first demonstration that regular consumption of a modest dose of resveratrol can enhance both cerebrovascular function and cognition in postmenopausal women and suggests that it may have the potential to reduce their heightened risks of stroke and cognitive impairment.